Strategi Pengembangan UMKM Coffe Shop di Kota Baturaja Kabupaten Oku - Dewi Yunita; Munajat Munajat; Yetty Oktarina; Fifian Permata Sari (SENTRI: Jurnal Riset Ilmiah, 2026)
One way to enjoy coffee is to experience it in various ways. One of these is the coffee shop, or what we commonly call a kedai kopi. As interest and the trend of visiting coffee shops have grown, more and more people are not only visiting to consume coffee, but also using coffee shops as venues for gatherings and reunions, meetings, or as places to work on assignments or simply relax after their daily routines. This study aims to analyze the internal and external factors of coffee shop SMEs. The research was conducted in OKU Regency, using a purposive sampling method with 80 SMEs as respondents. Data analysis employed a Likert scale and SWOT analysis. The results indicate that the strategies of coffee shop SMEs in Baturaja City for business development consist of four strategies: SO, WO, ST, and WT.